(untitled) (Journal of the College of Education for Women, 2019)
This study aims at discussing the theoretical and applicable parts of the reading comprehension to help the teachers of Arabic. This study shows that the students have a general weakness in reading comprehension. The researcher handles issues related to reading comprehension and to practicing exercises of the training strategies such as: dialogue, discussion, discussion questions, continuous training, group works. Such skills will be used to analyze a poem to see the level of the students’ reading comprehension and to develop the students’ skills. The study answers two questions:1- What is the reading comprehension from a theoretical perspective?2- How can we develop the skills of the reading comprehension from the practical and applicable perspective?